Case Study for Stroke: National Stroke Data Linkage Program - Kilkenny, Monique F; Kim, Joosup; Dalli, Lachlan; Eliakundu, Amminadab; Olaiya, Muideen (International Journal of Population Data Science, 2020)
Introduction Stroke is a leading cause of death and disability. Since 2012, our innovative national data linkage program, has enabled the successful linkage of data from the Australian Stroke Clinical Registry (AuSCR) with national and state-based datasets to investigate the continuum of stroke care and associated outcomes. Objectives and Approach Using stroke as a case study, in this symposium we will describe the use of linked data to undertake clinical and economic evaluations and contribute new knowledge for policy and practice. We have undertaken a range of iterative and innovative projects linking the AuSCR (used now in >80 public hospitals across Australia with follow-up survey of patients between 90-180 days) with various administrative datasets. Linkages with the National Death Index, inpatient admissions and emergency presentations, Pharmaceutical Benefits Scheme (PBS), Medicare Benefits Schedule (MBS), Aged Care services; Ambulance Victoria, Australian Rehabilitation Outcomes Centre and general practice network datasets (POLAR) have been achieved. Results The symposium will provide case studies and results from four data linkage projects involving the AuSCR: 1) Stroke123 (NHMRC: #1034415), a study to investigate the impact of quality of acute care on admission/emergency presentations and survival; 2) PRECISE (NHMRC:#1141848), a study to evaluate models of primary care involving linkages with PBS/MBS, aged care services and admissions/emergency data; 3) AMBULANCE: a study to investigate how pre-hospital care affects acute stroke care involving linkages with the ambulance and admissions/emergency datasets; and 4) POLAR: a study to understand the long-term management of stroke involving linkages with primary health data. Conclusion / Implications The National Stroke Data Linkage Program has been visionary and remains highly contemporary in the field of linked data. A unique feature of this program is the active participation of clinicians and policy-makers to ensure the evidence generated have direct benefits for accelerating change in practice and informing policy.